Sikap Ibu Terhadap Sisa Obat Pengobatan Di Salah Satu Puskemas Di Kota Bandar Lampung - Isnenia Isnenia; Siti Julaiha (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
The prevalence of leftover medicines that are still stored in households is still quite high, including people still storing medicines that have expired. Children are a vulnerable age group who often receive compounded and non-compounded medicines. The purpose of this study was to compare the attitudes of the two groups of mothers towards leftover compounded drugs and non-compunded drugs with assessment aspects namely storage of leftover drugs, reuse, and re-examination. This research is a quantitative-analytical research, non-experimental, with a cross-sectional design used in this study. Data was obtained from mothers of children who received treatment, carried out by guided interviews using an interview instrument containing 8 statements. The data was then processed statistically using the Chi Square test. The results showed that the age of most respondents was in the range of 26-35 years, the most recent education being high school, and as housewives, and using insurance. The percentage of respondents who showed a positive attitude on the aspects of remaining drug storage, reuse, re-examination in the compunded group (97.5%; 95%; 98.8%) showed a higher percentage than the non-compounded group (86.2%; 85% ; 97.5%). Both groups showed significant differences in aspects of leftover drug storage and reuse.